National Justice Agency List, 1992 ([Verlag nicht ermittelbar], 1994)
The National Justice Agency List is a master name and address file created and maintained by the Bureau of the Census for the Bureau of Justice Statistics. The file contains information for the following government justice agencies: law enforcement agencies, juvenile correctional facilities, local jails, state correctional facilities, and federal prisons. Variables include name of agency, address, state and region identification, telephone number, FIPS code, population, total workload, and number of professional and total employees.